Garantia da opinião pública : uma influência da mídia nas prisões preventivas - Barreto, Camilla Passos Oliveira (2019)
This paper aims at analyzing how the current constitutional order is challenged by the legal requirement of the guarantee of public order, as provided for in article 312 of the Code of Criminal Procedure, when interpretations of magistrates bring it closer to the relationship between crime and social repercussions projected from it. Therefore, it aims to demonstrate how compromised are the Judiciary, constitutional rights and guarantees, from this approximation between public opinion and the requirement of public order, when decrees of preventive detentions, mainly in mediated cases. The theme is relevant due to the scenario of excesses the country is going through. Its formulation, to a great extent, made use of the theoretical contribution brought by the “Guarantism” proposed by Luigi Ferrajoli. The path used to develop the research was based on a concrete case that demonstrates the susceptibility of public opinion and works on the idea of collective outrage caused by crime, punitive culture and the media’s power of influence on the modern individual’s mind. In addition, there is the semantic inconsistency of the term public order, often confused with public opinion, which leads to unnecessary detentions, distorting the very purpose of criminal law in the society of risk, and moving towards a system of exception. Consequently, it is confirmed that the Judiciary attracts the hopes of society to solve the problem of crime and impunity, demonstrating the inability of preventive detention when it is spectacular, since it would culminate in a subversion of the guarantist legal system, making innocuous criminal and constitutional procedural principles. Therefore, we chose the exploratory approach, and the qualitative and hypothetical-deductive methods. In addition, we used the bibliographic and documentary procedure from the beginning until its conclusion, so that, in the end, it is possible to achieve scientific advance and academic deepening about the topic proposed.